An Argument-Based Framework for Validating Formative Assessment in the Classroom - Gu, Peter Yongqi (Frontiers in Education, 2021)
The embedded and contingent nature of classroom-based formative assessment means that validity in the norm-referenced, summative tradition cannot be understood in exactly the same way for formative assessment. In fact, some scholars (e.g., Gipps 1994) have even contended for an entirely different paradigm with an independent set of criteria for its evaluation. Many others have conceptualised the validity of formative assessment in different ways (e.g., Nichols, Meyers, and Burling 2009; Pellegrino, DiBello, and Goldman 2016; Stobart 2012). This article outlines a framework for evaluating the argument-based validity of CBFA. In particular, I use Kane (2013) as a starting point to map out the types of inferences made in CBFA (interpretation and use argument) and the structure of arguments for the validity of the inferences (validity argument). It is hoped that a coherent and practical framework, together with its suggested list of inferences, warrants and backings, will help researchers evaluate the usefulness of CBFA. It is also hoped that teachers will find the framework useful in validating their own CBFA.